Impact of physical inactivity and sedentary behaviour on functional constipation in children and adolescents: a systematic review - Marc A Benninga; Morris Gordon; Shaman Rajindrajith; Wathsala Hathagoda; Shanaz Adil; Chandrani Kuruppu (BMJ Paediatrics Open)
Objective Lack of physical activity (PA) and sedentary behaviour (SB) have emerged as critical global health concerns in children and are believed to be associated with functional constipation (FC). The present study aims to explore this potential association.Design A comprehensive search of PubMed, Scopus, Web of Science, Embase, Cochrane Library and PsycInfo databases was conducted through 2023 using terms related to constipation and PA and SB in ages 0–18 years. Titles and abstracts were screened against eligibility criteria. Constipation was diagnosed using Rome (II–IV) criteria. Full-text reviews were reviewed, and data were extracted. Risk of Bias in Non-randomized Follow-up Studies of Exposure quality assessment tool was used to evaluate the risk of bias of studies.Main outcome measures We assessed the association between lack of PA/SB and FC.Results A total of 2170 titles were screened. Nine studies encompassing 3849 children from six countries were included. Of these, four were community/school-based studies, one was a birth cohort, three were case series and two were hospital-based case-controlled studies. All 10 studies assessed the association between PA and FC. Only three showed an association between lack of PA and FC. Five studies evaluated the effects of SB on FC, and only two reported a positive association. The methods used to assess PA/SB differed across the studies. All nine studies included in the systematic review were rated as having high risk of bias.Conclusions Despite numerous studies suggesting a link between insufficient PA/SB and FC, this systematic review did not uncover compelling evidence supporting such an association.